The Nordic Gene Bank’s Prunus clone archive in Finland: I Local races of sour cherry - Palonen, Pauliina; Uosukainen, Marjatta; Laurinen, Eeva; Parikka, Päivi; Kankila, Jyri (Agricultural and Food Science, 1998)
Morphological variation among 78 local races of sour cherry (Prunus cerasus L.) in the Nordic Gene Bank’s Prunus clone archive in Pälkäne in Southwestern Finland was examined. Each tree was described using 42 characteristics. On the basis of fruit characteristics, 32 samples were classified as morellos, 40 samples as amarelles, and 5 samples distinct from the other amarelles are proposed to be called Rymättylä-type cherries. One sample was found to be Prunus avium. Amarelle type cherries proved to be more self compatible than morello type cherries. In order to find hardy sour cherry cultivars with fruits of good flavour and fit for cultivation in Nordic conditions, the most promising local races from each group were selected for a comparative trial. Additionally, some local races were selected for further use in plant breeding. In 1994-1996, an increasing amount of severe bacterial canker symptoms was observed in the clone achive.